A Li-ion battery charger based on LDO regulator with pre-charge mode in 180 nm CMOS technology - Ouremchi, Mounir; El Khadiri, Karim; Qjidaa, Hassan; Jamil, Mohammed Ouazzani (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper presents a novel Li-Ion battery charger that utilizes a low-dropout (LDO) regulator and incorporates four control modes: low constant current mode, pre-charge current mode, fast constant current mode, and constant voltage mode. The charger aims to meet specific criteria such as high precision, high efficiency, and small form factor. Through simulation results, the following specifications were obtained using a 1.8 V supply in a 0.18 μm complementary metal–oxide–semiconductor (CMOS) technology: a trickle current of 124.7 mA, a pre-charge current of 466.94 mA, a maximum charge current of 1.06 A, and a charge voltage of 4.21 V. The proposed charger demonstrates an efficiency of 92%.